Tauberian Theorems by Weighted Summability Method - Loku Valdete; Braha Naim (National Academy of Sciences of Armenia)
In this paper, we will show a new Tauberian theorems defined by weighted Nörlund-Cesáro summability method.
Keywords: Mathematics; Approximations and expansions